2018
DOI: 10.1002/ange.201711761
|View full text |Cite
|
Sign up to set email alerts
|

Narrow‐Bandgap Chalcogenoviologens for Electrochromism and Visible‐Light‐Driven Hydrogen Evolution

Abstract: As eries of electron-accepting chalcogen-bridged viologens with narrowH OMO-LUMO bandgaps and low LUMO levels is reported. The optoelectronic properties of chalcogenoviologens can be readily tuned through heavy atom substitution (S,S ea nd Te). Herein, in situ electrochemical spectroscopyw as performed on the proof-of-concept electrochromic devices (ECD). E-BnV 2+ (E = Se,T e; BnV 2+ = benzyl viologen) was used for the visible-light-driven hydrogen evolution due to the strong visible-light absorption. Remarkab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 47 publications
3
3
0
Order By: Relevance
“…The bond lengths in the selenophene units for Ir-Se2F and Ir-Se3F are ca. 1.86 Å, similar to the reported data, while those in the thiophene and tellurophene units are 1.73 and 2.10 Å, respectively.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The bond lengths in the selenophene units for Ir-Se2F and Ir-Se3F are ca. 1.86 Å, similar to the reported data, while those in the thiophene and tellurophene units are 1.73 and 2.10 Å, respectively.…”
Section: Resultssupporting
confidence: 90%
“…The C–Se–C bond angles in the aryl selenophene units are 86.2(4)° for Ir-Se2F and 85.6(3)° for Ir-Se3F , similar to the reported data . In their analogous scaffolds with thiophene and tellurophene units, the C–S–C bond angles in thiophene units and C–Te–C bond angles in tellurophene units are ca. 90 and 80°, respectively.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…They are widely used in gas storage and separation, chemical sensing, catalysis, biomedicine, and optoelectronic materials because of many advantages such as easy synthesis, easy to make film, and good flexibility. The positive photochromic behavior of viologen compounds has been widely studied because of the obvious redshift of absorption bands after photoinduced electron transfer. We have previously found that infinite π-stacking of viologen cations is an effective approach to synthesize photochromic semiconductors. , Therefore, it is possible to use viologen units to prepare photochromic semiconductive HOFs with broadband photoelectric response through a careful design of hydrogen-bonding networks.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] The emerging development of tellurium compounds is apparent from the applications in catalysis, [18][19][20][21] coordination, [22][23][24][25][26] and optoelectronic materials. [27][28][29][30][31][32][33][34] The low Pauling electronegativity and high polarisability of tellurium lead to strong secondary bonding interactions (SBIs) and/or hypervalent states. 12,[35][36][37][38] Meanwhile, embedding Te onto the π-scaffolds of organotellurium compounds will narrow HOMO-LUMO energy gap, [39][40][41][42] produce intermolecular Te•••X SBIs in solid state, [43][44][45] and alter the chemical behaviors.…”
Section: Introductionmentioning
confidence: 99%